Selection of Coagulant with Consideration of Sludge Characteristics for Treatment of Industrial Wastewater Containing High Strength Mixed Surfactants - Tongchai Sriwiriyarat (Science Faculty of Chiang Mai University, 2019)
An attempt was made in this study to compare the sludge characteristics between aluminum sulfate (alum) and polyaluminum chloride (PACl) in additional to the optimum initial pH and dosage so the selection of the coagulant could be made for the coagulation-flocculation process treating specifically the wastewater containing high strength mixed surfactants generated from the industry manufacturing soaps, detergents, and various consumer-products. The sludge settling velocity, sludge volume index (SVI), and dewatering properties of each coagulant were evaluated to indicate the sludge characteristics. The optimum initial pH and chemical dosage of each coagulant were also conducted in a Jar Test apparatus for the simultaneous removals of organic matters indicated as Total Chemical Oxygen Demand (TCOD), anionic surfactants indicated as Total Active Ingredients (TAI), Total Suspended Solids (TSS), and turbidity. The experimental results indicated that the optimum pH value and dosage of alum were 8 and 600 mg/L, respectively, resulting in the TSS, turbidity, TCOD, and TAI removal efficiencies of 96.6, 90.4, 85.5, and 97.9%, respectively. The same dosage of PACl at the concentration of 600 mg/L was required under the optimum pH of 6, providing the TSS, turbidity, TCOD, and TAI removal efficiencies of 99.2, 99.3, 83.3, and 97.9%, respectively. The PACl provided more TSS and turbidity removal efficiencies than the alum for the wastewater containing high strength mixed surfactants. For sludge characteristics, the alum sludge had higher settling rate, generated lower sludge volume, and was easier to be dewatered than the PACl sludge. The explanation was that the destabilization mechanism of alum was sweep flocculation resulting in compact aluminum hydroxide precipitates, but the mechanism of PACl was interparticle bridging due to high concentration and aging providing less dense and loose structure of flocs. The PACl was superior to the alum for TSS and turbidity removals as a result of interparticle bridging destabilization mechanism. In conclusion, the alum was suggested as the coagulant for this industrial wastewater as it provided approximately the same TSS, TCOD and TAI removal efficiencies as the PACl even though the turbidity removal efficiency was lower than about 9% because it generated better sludge characteristics.